2021
DOI: 10.1037/emo0000648
|View full text |Cite
|
Sign up to set email alerts
|

Laterality and (in)visibility in emotional face perception: Manipulations in spatial frequency content.

Abstract: It is widely agreed that hemispheric asymmetries in emotional face perception exist. However, the mechanisms underlying this lateralization are not fully understood. In the present study, we tested whether (a) these asymmetries are driven by the low spatial frequency content of images depicting facial expressions, and (b) whether the effects differed depending on whether the emotional facial expressions were clearly visible or hidden (i.e., embedded in low spatial frequencies). The manipulation sheds light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 58 publications
6
13
1
Order By: Relevance
“…We hypothesized an overall LVF/RH bias for easily recognized chimeric faces (emotional intensity of 100%) across all six basic emotions, regardless of emotional valence, which is in line with the overall RH bias reported previously (Bourne, 2010;Hausmann et al, 2021;Sackeim & Gur, 1978; for a review, see Gainotti, 2019). In line with Carbary et al (2001Carbary et al ( , 2002, we also predicted that the ECFT bias decreases as the emotional facial expressions become less emotionally distinct.…”
supporting
confidence: 87%
“…We hypothesized an overall LVF/RH bias for easily recognized chimeric faces (emotional intensity of 100%) across all six basic emotions, regardless of emotional valence, which is in line with the overall RH bias reported previously (Bourne, 2010;Hausmann et al, 2021;Sackeim & Gur, 1978; for a review, see Gainotti, 2019). In line with Carbary et al (2001Carbary et al ( , 2002, we also predicted that the ECFT bias decreases as the emotional facial expressions become less emotionally distinct.…”
supporting
confidence: 87%
“…Indeed, even isolated face parts (eyes, mouth) are better recognized and more strongly represented in right inferior occipital gyrus when they were presented at typical, rather than reversed, visual field locations (de Haas et al, 2016). There are also left visual-field advantages for many aspects of face perception, including emotion perception (e.g., Adolphs, 2002; Burt & Perrett, 1997) and recent evidence indicates that low spatial frequencies are not generally sufficient to induce a left visual field bias in emotion perception under free-viewing conditions (Hausmann, Innes, Birch, & Kentridge, 2019). These issues deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Three major theories of hemisphere asymmetries in emotion processing-the RHH, VSH, and AWH-predict right hemisphere dominance for negative facial expressions of disgust, fear, and sadness. This is observed in many studies (e.g., Bourne, 2010;Kumar and Srinivasan, 2011;Rahman and Anchassi, 2012;Innes et al, 2016;Damaskinou and Watling, 2018;Kajal et al, 2020;Hausmann et al, 2021), however, some studies observe left hemisphere dominance for one or more of these expressions (Prete et al, 2014b(Prete et al, , 2015aBurt and Hausmann, 2019;Bublatzky et al, 2020;Lai et al, 2020;Stanković and Nešić, 2020). The present research investigated whether tasks that require identifying the linguistic category of facial expressions are more likely to produce left hemisphere dominance than tasks that do not require this information.…”
Section: Discussionmentioning
confidence: 73%
“…Critically, despite the important differences between the theories, the RHH, VSH, and AWH are similar in that they all predict right hemisphere dominance for the negative facial expressions of sadness, fear, and disgust. This effect is observed by many studies (e.g., Bourne, 2010;Kumar and Srinivasan, 2011;Rahman and Anchassi, 2012;Innes et al, 2016;Damaskinou and Watling, 2018;Kajal et al, 2020;Hausmann et al, 2021). Nonetheless, some studies have observed left hemisphere dominance for one or more of these expressions under particular experimental conditions (Prete et al, 2014b(Prete et al, , 2015aBurt and Hausmann, 2019;Bublatzky et al, 2020;Lai et al, 2020;Stanković and Nešić, 2020).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation